(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2021)
The breeding biology of the common kingfisher (Alcedo atthis) was studied from 2008 to 2011 in Dhaka North City Corporation and Savar Upazilla. The breeding season was April to September. It laid 3 to 7 glossy white, almost round eggs with a size of 2.5±0.3 cm length, 2.2±0.3 cm breadth, and 5.3±0.7g weight. It incubated for 16 to 21 days. During hatching, the hatchlings’ weight ranged from 8.5 to 10.5 g and total body length from 43.2 to 58.6 mm whereas, it was 30.1 to 32.7 g and 151 to 155.5 mm, respectively, during fledging. Hatching success was 83.3%. Stolen by people (13.9%) and infertility (2.8%) were the causes of egg loss. The young birds fledged out after 21 to 27 days of hatching. A total of 56.7% of nestlings were unable to fly due to stolen (43.3%), deaths due to unknown reasons (6.7%) and deaths due to natural disaster (6.7%). The breeding success was 36.1% in relation to eggs laid and 43.3% in relation to eggs hatched. J. Asiat. Soc. Bangladesh, Sci. 47(1): 23-34, June 2021